Relationship between dental age, skeletal maturity and chronological age in young orthodontic patients. - Lund, Erlend; Tonje, Tømmervold (UiT Norges arktiske universitet, 2014)
Abstract Objectives: The aim of this study was to find out in what extend the dental age and skeletal maturity relate with the chronological age, in a sample of 50 subjects in the range 7 – 16 years old, from the Northern part of Norway Subjects and methods: The subjects were all patients who had received/were undergoing orthodontic treatment at the Public Dental Service Competence Centre of Northern Norway (TkNN). The sample consisted of 25 males and 25 females, from 7-16 years in age. The subjects were selected to represent 5 different age groups, and each group consisted of 5 boys and 5 girls. The inclusion criteria were age between 7 and 16 at the time the OPG and lateral cephalogram were taken, and presence of the 7 left side mandibular teeth. Dental age was assessed on panoramic radiographs by using Demirjian and Goldstein radiographic analysis. This method is based on ratings of radiographs of the seven left side teeth of the mandible. Skeletal maturity was assessed by using the Cervical Vertebral Maturation method, which is a method for assessing adolescent growth stage and for predicting the start of the pubertal growth spurt in orthodontic patients. Results: There was a strong correlation between all measured variables. The correlation coefficients between chronological age and cervical stage were 0,871 for girls and 0,902 for boys, between chronological age and dental age 0,900 for both girls and boys, and between dental age and cervical stage 0,846 and 0,900 for girls and boys respectively. Chronological age was significantly higher than dental age among both boys (P=0,020) and girls (P=0,002) and the difference was more marked in girl. In average, girls reached their pubertal growth spurt (CS 3) at a younger age than boys. Dental age in the end of the pubertal growth spurt (CS 4) varied considerably more among girls (range 10,1-15,2 years) as compared with boys (range 13.1-14.7 years). Conclusion: In this sample, the chronological age was generally higher than the dental age. There were strong ...